Fablab teacher efficacy: A framework for designing effective professional development for Fablab teachers and facilitators - Aydeniz, Mehmet; Stone, Micheal (American Journal of STEM Education, 2026)
FabLabs foster 21st-century skills, yet their integration into K-12 classrooms remains limited. This study aimed to design and validate a FabLab Teacher Self-Efficacy Instrument, and then pilot it in a FabLab-centered professional development program. A 45-item Likert survey was used to measure teacher confidence across planning, instruction, and assessment. Teachers reported the highest efficacy in planning (M = 3.78), followed by instruction (M = 3.64), and the lowest in assessment (M = 3.19). Qualitative findings revealed barriers, including a restrictive school culture and limited instructional time. Participants emphasized the importance of hands-on training, collaboration, and sustained support to build both pedagogical and technical confidence for meaningful FabLab integration.